Complete Malleus Removal for Cholesteatoma: A Multivariate Analysis of Ossiculoplasty Success and Residual Disease. (January 2018) - Shapiro, Scott; Bennett, Donald; Wetmore, Stephen; Cassis, Adam
Objective: Determine the effect of complete malleus removal during canal wall up tympanomastoidectomy for cholesteatoma on ossiculoplasty success and rate of residual cholesteatoma. Methods: We reviewed the operative, audiogram, and clinical reports of patients who underwent canal wall up tympanomastoidectomy for cholesteatoma between 2009 and 2016 at a tertiary academic medical center with at least 8 months of follow-up after surgery. To control for extent of disease, we independently catalogued the subsites of the middle ear and mastoid that cholesteatoma involved from each operation. We performed multivariate logistic regression to determine the independent effect of complete removal of the malleus on the rate of residual disease and success of ossiculoplasty. Results: One hundred eighty surgeries were included in the analysis. For ossiculoplasty success, the adjusted odds ratio of complete malleus removal was 1.7 (95% CI, 0.43-7.0, P = .43), which was not statistically significant. For residual disease, the adjusted odds ratio of complete malleus removal versus not was 0.29 (95% CI, 0.074-1.1, P = .076), which approached but did not meet statistical significance. Conclusion: Though complete malleus removal does not independently decrease the rate of residual cholesteatoma, it may be a safe technique as it did not compromise ossiculoplasty success.